Shape preserving approximation for unbounded multivariate functions - Kareem, Mayada Ali; Kamel, Rehab Amer; Hussain, Ahmed Hadi (Journal of interdisciplinary mathematics, 2022)
The purpose of this research is to present a new method for creating polynomials and spline approximation to unbounded multivariate functions in L ρ , β ([-1, 1] I ) using ordinary modulus of smoothness, Sendov-Popov modulus and Ditzian-Totik modulus.